Exploring the Relationship Between Visual Aesthetics and Social Commerce Through Visual Information Adoption Unimodel - Yang, Yongzhong; Tang, Yunyan; Zhang, Yu; Yang, Ruo (Frontiers in Psychology, 2021)
The visual revolution and attention economy of the digital world have put visual aesthetic communication into the primary position of social media marketing. However, this phenomenon remains underexplored within social commerce research. This study thus develops a visual information adoption unimodel (VIAUM), to explore the relationship between visual aesthetics and social commerce intentions. Users with social commerce experience are invited to complete our online survey, and 321 valid data are collected. The results reveal that visual aesthetics has direct and indirect (via perceived usefulness) effects on the social commerce intention of users. Besides, interdependent self-construal (InterSC) strengthens the direct effect between visual aesthetics and social commerce intention. In contrast, independent self-construal weakens the mediation effects of perceived usefulness. This study is among the first attempts to empirically examine the intervening mechanism and boundary conditions between the visual aesthetics of self-presentation of micro-celebrity and the social commerce intention of consumers.